Family Dynamics of Patients with Alzheimer’s Disease Before and After its Onset - Sánchez Márquez, Nery Isabel; Bilbao Fuentes, Dora Beatriz (Pensando Psicología, 2018)
Introduction: This research describes the family dynamics of patients diagnosed with Alzheimer’s disease in the municipality of Barrancabermeja (Colombia) in order to approach the state of the family system and how it is affected by this diagnosis.Aim: To describe family structure before and after the diagnosis based on the family genogram, to define family dynamics before and after the diagnosis of Alzheimer’s disease, and to identify personal, family, social and economic impacts on each family group.Materials and methods: Qualitative research; a sample of nine  participating families was completed to collect information for the family genogram.Results: The impact of this disease on families is directly related to the stage the patient is on and the symptoms associated with it. As the disease progresses, the subject shows increased dependence due to deterioration of his cognitive and physical functions. Thus, the family provides more care to the patient, which involves great effort, time, adaptation in the lifestyles of family members and reorganization of the family unit.Conclusions: The diagnosis of the disease produces structural and functional changes that alter family dynamics, which are closely related to personal and family life cycles, the degree of deterioration and thestage the patient is on. Family typology and affective bonds established before the diagnosis are decisive for coping with situations that cause risis and instability within the nucleus and to the primary caregiver.
Keywords: attitudes; adaptability; cohesion; communication; primary caregiver; family dynamics; Alzheimer’s disease; roles; family system